Users' satisfaction level on maintenance management practice in private Hospital Manjung and Ipoh / Naquib Halmi and Alia Abdullah Saleh - Halmi, Naquib; Abdullah Saleh, Alia (2019)
The hospital (health-care) building is a basic need for all and represents, perhaps the most difficult group of largely public sector buildings to maintain because of their complex engineering services and their heterogeneous nature. Besides, the facility manager needs to begin to develop the best maintenance strategy on early stage based on the vision, mission and goals of the organization in the hospital to keep in better performance. Furthermore, safety and hygiene considerations make the condition of these buildings a particularly sensitive issue. The aim of this research is to provide an overview of the types of maintenance strategies applied to maintain facilities while satisfying the end user. This paper will identify the maintenance management best practices that affecting users' satisfaction. The first objective of this research is to identify the maintenance management practices implemented in private hospitals. The next objective is, to determine and rank the performance that influence the users' satisfaction level and for the last objective, to recommend the best practice of maintenance management in private hospitals. To achieve the objectives of this research, the questionnaires were distributed to the maintenance management staff and users of hospital. The total of 20 questionnaires were distributed towards relevant respondents like building managers, building maintenance management workers and users. The totals of completed questionnaires received were 15 to designed an information for descriptive and ranking analysis. Results for this analysis can be concluded that there are 4 main factors the affecting users' satisfaction that are maintenance management staffs are lack of knowledge for hospital building, the execution of works takes time due to limited staff, procedure to complaint delayed and lack of supervision.